ETracer: An innovative object tracking and tracing platform - Konstantinidis, Vasileios; Papatheocharous, Efi; Andreou, Andreas S. (My University, 2011)
Near real-time tracking of objects is becoming a critical requirement in transportation business today since competition is increasing and customers are becoming more demanding in obtaining information on services and delivery of products. The technological advancements in the fields of networking (e.g., 3G, HSDPA), near field communications (e.g., RFID) and location identification (e.g., AGPS) provide the potential for the creation of an advanced intelligent tracking platform that identifies and captures an object all across its lifecycle. In the current paper we present such an innovative platform; eTracer which is an end-to-end near realtime tracking platform for objects. In addition, the architecture of eTracer is analyzed and the research issue of reducing the computational intensiveness of processing is also discussed.
Keywords: Business intelligence | Logistics management | Object tracking | RFID Processing | Tracing